Suplementación con la leguminosa arbustiva matarratón (Gliricidia sepium) en la alimentación de pollos de engorde - Bazantez Rivas, Josselyn Maribel (2024)
The supplementation of mousetrap flour (Gliricida sepuim) was evaluated where treatments were carried out to analyze the growth and fattening behavior. Each treatment corresponds to a weight phase and a level of supplementation (10, 15 and 20%). In the research work, 96 chickens were used and the supplementation of the Matarraton flour was evaluated from the second week until completion. The treatments of four experiments were: (T0) formulated with 100% commercial balance plus water (T1) formulated with 100% commercial balance plus 10% mousetrap flour plus water (T2) formulated with 100% balance commercial plus 15% Matarraton flour plus water (T3) formulated with 100% commercial balance plus 20% Matarraton flour plus water. This research work was carried out in 6 weeks where the weight gain of each subject was evaluated of the treatment, different weights could be observed but nevertheless it was in T3 (20% mousetrap flour) that a notable difference in weight gain was obtained compared to the other treatments, thus having a final weight of 32974.57 gr with a feed conversion of 1.14. And T1 was the treatment with the lowest final weight gain of 32,592.6 gr with a feed conversion of 1.18. The objective of this work is to evaluate the use of mousetrap (Gliricidia sepium) as a supplement in the feed for broiler chickens at 10%, 15% and 20% flour. In the research, a completely randomized design was used, all variables were recorded week by week for 6 weeks since the research focused on the supplementation of marraton flour in broiler chickens that were fed 2 times a day and the provision of water.